Impact of a Concha Bullosa on Nasal Airflow Characteristics in the Setting of Nasal Septal Deviation: A Computational Fluid Dynamics Analysis. Issue 4 (July 2020) - Li, Lifeng; Zang, Hongrui; Han, Demin; Ramanathan, Murugappan; Carrau, Ricardo L.; London, Nyall R.
Background: A concha bullosa (CB) of the middle turbinate is frequently observed on the nondeviated side of patients with a nasal septal deviation (NSD). However, the impact of the CB on nasal airflow characteristics in patients with NSD has been incompletely defined. Objective: The purpose of this study was to evaluate the impact of a CB in patients with NSD on nasal airflow characteristics using a computational fluid dynamics (CFD) approach. Methods: Twenty patients with NSD and a unilateral CB of the middle turbinate on the nondeviated side (study group) were recruited. Another 20 patients with NSD without the formation of a CB (control group) were also enrolled. Using CFD, the maximal airflow velocity, nasal resistance, maximal wall shear stress, and minimal temperature in the bilateral nostrils of each group were assessed. Moreover, the volume of the nasal tract, surface area-to-volume ratio, and the total nasal resistance were compared between the study and control groups. Results: In the study group, no significant differences of airflow dynamics between the bilateral nasal cavities were observed. In the control group, however, there were statistically significant differences for maximal airflow velocity, nasal resistance, maximal wall shear stress, and minimal airflow temperature between the bilateral nostrils. The surface area-to-volume ratio and total nasal resistance in the study group was significantly higher and the nasal volume was significantly decreased than that in the control group. Conclusion: CB of the middle turbinate on the nondeviated side of patients with NSD rendered airflow characteristics more evenly distributed between the bilateral nostrils as assessed by CFD. From an aerodynamics perspective, a CB may represent a compensatory action to normalize airflow dynamics. However, a CB may also result in constriction of the ipsilateral nasal cavity.